Relatedness of penicillin-binding protein 1a genes from different clones of penicillin-resistant Streptococcus pneumoniae isolated in South Africa and Spain. - Martin, C (1992)
Penicillin-resistant strains of Streptococcus pneumoniae have been common in South Africa and Spain for several years. Multilocus enzyme electrophoresis identified one clone of capsular type 6B which was prevalent in Spain and another clone of type 23F that was present in both countries. Genes for penicillin-binding proteins (PBPs) in penicillin-resistant strains are often mosaics where parts of the pneumococcal genes are replaced by homologous genes from other species. We have compared the mosaic structures of the PBP 1a genes from the two clones as well as from genetically distinct South African isolates. Four classes of mosaic PBP 1a genes were found that contained blocks of sequences divergent by 6-22% from those of sensitive genes; two classes contained sequences coming from more than one external source. Data are presented showing that the PBP 1a genes from the 23F and the 6B clone are related, and that the two PBP 1a genes from the South African isolates are also related. We suggest that the type 23F clone originated in Spain prior to distribution into other continents.